2012
DOI: 10.28930/jitkt.v4i2.7799
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION OF SECONDARY METABOLITES COMPOUNDS, ANTIBACTERIAL AND ANTIOXIDANT ACTIVITIES ON THE METHANOL EXTRACT OF SEA CUCUMBER Stichopus hermanii

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Papaya seeds were washed, cleaned, and dried until the water content was reduced. Next, dried papaya seeds were mashed using a blender and weighed 500 g. Then the smooth papaya seeds were extracted according to the Harborne method in Rasyid (2012). First, the smooth papaya seeds were macerated in a jar using 96% ethanol solvent and stirred using a stirring rod, then covered with aluminum foil and allowed to stand for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Papaya seeds were washed, cleaned, and dried until the water content was reduced. Next, dried papaya seeds were mashed using a blender and weighed 500 g. Then the smooth papaya seeds were extracted according to the Harborne method in Rasyid (2012). First, the smooth papaya seeds were macerated in a jar using 96% ethanol solvent and stirred using a stirring rod, then covered with aluminum foil and allowed to stand for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Even though the MDA level at normal group is higher than DM group, which is still below the normal limit of the MDA level in rats. Sea cucumber and combined groups showed that the level of serum MDA was not significantly different from the normal group, Rasyid (2012) reported that sea cucumber showed antioxidant activity and possessed bioactive compounds in steroids and saponin form. Marrelli et al (2016) reported that saponin could demonstrate the ability to reduce free radicals like malondialdehyde (MDA).…”
mentioning
confidence: 89%
“…Blood glucose levels while fasting at the end of the study in the sea cucumber and spirulina-feeding group with values not significantly different from the normal wound control group with a significant decrease, namely the golden sea-cucumber-feeding group of 77.16% and the gama-feeding group of 77.05%, which is suspected to be related to the content of the active substance in these preparations. According to [9] and [10] golden sea cucumber extract contains steroids, saponins, alkaloids and triterpenoids and has antioxidant activity through inhibition of DPPH (1,1-diphenyl-2-picrylhydrazyl). Likewise with the spirulina-feeding group which had a decrease of 67.68% (the spirulina-feeding group of golden sea cucumbers) and 70.88% (the spirulina-feeding group of gama sea cucumbers), spirulina ethyl acetate extract has antioxidant activity through inhibition of DPPH and contains active substances of phenolic compounds, triterpenoids, steroids, flavonoids and saponins.…”
Section: Blood Glucose Levelsmentioning
confidence: 99%